Case report: Hepatic inflammatory pseudotumor-like follicular dendritic cell sarcoma: a rare case and review of the literature - Yan, Shuai; Yue, Zhiqiang; Zhang, Peng; Yuan, Liuxia; Wang, Huixuan; Yin, Fei; Ju, Linglin; Chen, Lin; Cai, Weihua; Ni, Yi; Wu, Jinzhu (Frontiers in Medicine, 2023)
Inflammatory pseudotumor-like follicular dendritic cell sarcoma (IPT-like FDCS) is a rare subtype of follicular dendritic cell sarcoma (FDCS) that primarily occurs in the liver and spleen. The etiology of IPT-like FDCS is unknown, and it has nonspecific clinical manifestations, imaging performance and laboratory test results. Recently, a patient with IPT-like FDCS was admitted to our hospital because of abdominal distension and anemia. Over the past 3 years, the patient has been followed up after a liver mass was found in a physical examination. The lesion gradually enlarged and caused compression symptoms. In November 2022, a tumor with a diameter of approximately 20 cm was found in the right posterior lobe of the liver after abdominal enhanced Magnetic resonance imaging (MRI) in our hospital. Liver tumor biopsy before the operation revealed a large number of hyperplastic plasma cells and a small number of spindle cells, and the spindle cells were atypical. After a complete examination, the patient underwent liver resection. Pathology after surgery confirmed liver IPT-like FDCS.